FACTORS AFFECTING THE HIGHER EDUCATION STUDENT’S PERFORMANCE IN ONLINE LEARNING DURING THE PANDEMIC - Wan Zukri Wan Abdullah; Mohd Fakri Muda; Amminuddin Ab Latif; Rasyad Afif Ibrahim; Md Hamzaimi Azrol bin Md Baharudin; Rafizah Mohamed Nordin; Norizzati Ibrahim; Nor Jihan Abd Malek (Journal of Islamic, Social, Economics and Development, 2023)
The utilisation of information technology to facilitate and enhance teaching and learning is increasingly prevalent in higher education, particularly in response to the worldwide outbreak of the Covid-19 pandemic, which necessitates the thorough adoption of online instructional approaches. Nevertheless, the extent to which students engage and excel in an online learning environment remains to be determined, particularly with regard to the quality of their academic achievements. Therefore, the objective of this study is to examine the perspectives and suggestions of experts about the identification of elements that may impact the academic performance of students engaged in online learning. Moreover, these results provide conclusions and recommendations for addressing the challenges in student performance that arise from the use of online learning systems, as informed by expert viewpoints. In this study,the Nominal Group Technique (NGT) has been employed as the primary methodology. This approach entails the participation of six experts who possess extensive experience in online teaching and addressing challenges related to student performance in non-physical instructional settings. A comprehensive set of ten (10) factors has been defined to gather expert comments regarding the importance of their influence on educational performance in the context of online learning. The data analysis methodology employed in the Nominal Group Technique (NGT) is distinguished by its simplicity, as it focuses on the computation of agreement percentages. There is a contention that when the percentage degree of agreement exceeds 70% or more, it indicates the acknowledgment and approval of both the component and element. The results found that all the factors considered have been accepted as factors that can affect achievement and performance among higher education students. This study provides an opportunity for future research to look deeper into the difference in student performance between conventional learning methods and online learning.